2002
DOI: 10.1051/vetres:2002020
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the hepatic NK cell response during the early phase of Fasciola hepatica infection in rats

Abstract: -The in situ distribution of NK cells in rat liver during the first 28 days of an experimental infection with F. hepatica was investigated. NK cells were distributed homogeneously throughout the hepatic parenchyma in uninfected animals. The total number of hepatic mononuclear cells increased significantly following infection, but the proportion of NK cells did not change. After infection, these cells were found around the portal space, around the centrolobular vein, in the periportal fibrosis and in the band o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…Previous studies of Th cytokines in rats concerned only the early stages of fascioliasis. During the first 2 weeks of infection, F. hepatica induced a transient Th0 cytokine profile, followed by down-regulation of the cellular response and the induction of a Th2 cytokine profile [12,13]. In infected rats, the presence of higher levels of IL-10 and IL-4 at 7 weeks after infection and of IL-10 at 10 weeks after infection was observed, findings that agree with previous observations regarding early infection.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Previous studies of Th cytokines in rats concerned only the early stages of fascioliasis. During the first 2 weeks of infection, F. hepatica induced a transient Th0 cytokine profile, followed by down-regulation of the cellular response and the induction of a Th2 cytokine profile [12,13]. In infected rats, the presence of higher levels of IL-10 and IL-4 at 7 weeks after infection and of IL-10 at 10 weeks after infection was observed, findings that agree with previous observations regarding early infection.…”
Section: Discussionsupporting
confidence: 90%
“…In the rat, fascioliasis is considered to be an advanced chronic disease from 100 days after infection onward [10,11]. Previous studies performed on T helper cytokines in rats basically concerned the early stages of fascioliasis, suggesting that Fasciola species, similar to other helminth parasites, induce a polarized Th2 response [12][13][14]. However, to our knowledge, no studies have investigated the immune response of Fasciola species in the advanced chronic stage in a rat model.…”
mentioning
confidence: 99%
“…In contrast, several other studies, in which NK cells were depleted by anti-NK1.1 treatment (thus depleting both NK cells and NKT cells), showed no significant impact on host immune responses to Trichuris muris (28) and Schistosoma mansoni (29). Similarly, studies using a rat model of Fasciola hepatica infection concluded that NK cells do not play a significant role in the course of infection (30).…”
Section: Discussionmentioning
confidence: 86%
“…Recently, a secreted protein from the human hookworm Necator americanus was found to bind NK cells directly and induce IFN-␥ production (21). In rodent models of Trichuris muris (22), Schistosoma mansoni (23), and Fasciola hepatica (24), no significant role for NK cells in host immunity has been detected. In a mouse model of Litomosoides sigmodontis infection, NK cells were found to be important in host defense (9), while in a SCID model of B. malayi infection, NK cells were found to be essential for worm development (10).…”
Section: Discussionmentioning
confidence: 99%